Handbook for clinical investigators - Kirkpatrick, Christopher T. (Taylor & Francis, 1999)
This text is for at clinical investigators, usually physicians, especially those conducting clinical trials to evaluate new drugs. It is the product of a respected clinical investigator sharing his experiences and insights, so that others can share in the excitement of clinical research while avoiding some of the pitfalls that inevitably beset the clinical trialist. The book provides practical advice on how to interact with various "monitors", auditors and project leaders running the trial. It also gives advice on how to recruit patients to the trials. The author looks at subjects such as allocation of time, space and staff. This book is predominantly aimed at doctors performing clinical trials for pharmaceutical companies and will be of great help to Heads of Clinical Research in pharmaceutical companies - also to academic staff in university clinical departments, particularly pharmacology